Preparation of Law Creating Work Based On Law No. 12 of 2011 - Muhammad Ihza Prayogo; Evi Retno Wulan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The formation of Indonesia laws is stipulated by the 1945 Constitution regarding Article 96 of Law No. 12 of 2011, which emphasizes the importance of public participation in every stage of lawmaking. However, in reality, the process of forming laws and regulations, such as in the case of the Job Creation Law, does not involve maximum public participation. This has led to the emergence of dissatisfaction among the public with the resulting omnibus law concept. To achieve the goals of democracy and social justice, the government needs to improve the participation mechanism by opening up space for public input. This process must be conducted transparently from the planning stage to enactment so that the public feels involved and heard. Without active participation from the public, legal products could potentially be unaccepted and deemed illegitimate. Therefore, efforts to implement omnibus law as a solution to simplify regulations must be accompanied by concrete steps to involve the community. Otherwise, the ideals of legal reform will be difficult to achieve.